We took to the woods - Rich, Louise Dickinson, 1903-1991.; Kimber, Robert; Arlen, Alice (Camden, Me. : Down East Books, 1970)
In her early thirties, Louise Dickinson Rich took to the woods of Maine with her husband. They found their livelihood and raised a family in the remote backcountry settlement of Middle Dam, in the Rangeley area. Louise made time after morning chores to write about their lives.
Reprint. Originally published: Philadelphia : J.B. Lippincott, c1942.
Louise Dickinson Rich is a Maine author.
Keywords: Rich, Louise Dickinson, -- 1903-1991.; Country life -- Maine; Maine -- Description and travel